(untitled) (Global Journal of Science Frontier Research, 2025)
A method of controlling an asynchronous electric drive based on measuring and regulating the reactive power of an induction motor is proposed The independence of the rotor flux and the electro mechanical moment from the change in the parameters of the induction motor is ensured a continuous range of speed regulation including zero and fast-acting regulation is ensured